P213 The Impact Of Sleep Disordered Breathing On Peripheral Muscle. (10th November 2014) - Mandal, S; Dhir, T; Vaughan-France, A; Suh, ES; Hart, N
Abstract : Introduction: Chronic obstructive pulmonary disease is characterised by peripheral muscle wasting with consequent reduction in muscle strength and function. In this cohort of patients a reduction in muscle strength correlates with morbidity and mortality. Less well known are the characteristics of muscle in patients with sleep disordered breathing (SDB), a disease state that can also be dominated by inflammation, breathlessness and hypoxia. We sought to examine the impact of sleep disordered breathing on peripheral muscle size and strength. Method: 51 subjects were recruited: 15 healthy controls (HC) with a normal body mass index (BMI, <25 kg/m 2 ), 16 overweight and obese individuals with no SDB controls (SO), and 20 obese subjects with obstructive sleep apnoea (OSA). Subjects underwent measurements of Rectus Femoris Cross Sectional Area (RFCSA ) and quadriceps maximal voluntary contraction (QMVC). Handgrip strength and six minute walk distance (SMWD) were also recorded. Results: As expected there were differences in BMI between the groups. There were also significant differences in muscle strength and RFCSA when corrected for body weight between HC and OSA groups and between SO and OSA groups, but no differences between HC and SO groups (Table 1 ). The SO group demonstrated higher measurements of strength and RFCSA than the HC group, however, the OSA group had lower measurements than both the HC and SO group. This translated to a functional difference as measured by the SMWD, again demonstrating the longest distance in the SO group and shortest in the OSA group. Discussion: This study has demonstrated that in those with a BMI ≥25 kg/m 2 there appears to be a beneficial effect of excess weight on peripheral muscle size, strength and function; this may be due to the extra load carried by these individuals exerting a training effect on the muscles. However, in those who are obese with SDB, the SDB seems to exert a negative effect on muscle size, strength and function which may be a result of the inflammation and hypoxia SDB can cause.